MicroRNA miR-145-5p regulates cell proliferation and cell migration in colon cancer by inhibiting chemokine (C-X-C motif) ligand 1 and integrin α2 - Wei Zhuang; Tao Niu; Zhen Li (Taylor & Francis, 2021)
Colon cancer (CC), which has high morbidity and mortality, can be regulated by microRNAs. This study aimed to investigate the regulatory function of microRNA miR-145-5p in CC cells. Bioinformatics analysis was used to screen key genes in CC. The expression of miR-145-5p, chemokine (C-X-C motif) ligand 1 (CXCL1), and integrin α2 (ITGA2) in CC was confirmed by quantitative reverse transcription polymerase chain reaction and western blotting. After cell transfection, changes in proliferation and migration in CC cells were detected using the cell counting kit-8 (CCK-8), colony formation assay, and wound healing assay. A luciferase assay was conducted to confirm the interactome of miR-145-5p, CXCL1, and ITGA2 in CC cells. Bioinformatics analysis confirmed that CXCL1 and ITGA2 were key genes in CC. After performing several cell functional experiments, the results confirmed that upregulation of miR-145-5p attenuated proliferation and migration of CC cells. Luciferase assay and western blotting confirmed that CXCL1 and ITGA2 were targets of miR-145-5p, and their expression in CC could be suppressed by miR-145-5p. In conclusion, miR-145-5p is a tumor suppressor in CC and can inhibit the expression of CXCL1 and ITGA2.
Keywords: Biophysics; Biochemistry; Cell Biology; Genetics; Molecular Biology; Pharmacology; Biotechnology; Chemical Sciences not elsewhere classified; Immunology; Biological Sciences not elsewhere classified; Developmental Biology; Cancer; Hematology; Infectious Diseases